The impact of the Directive on Representative Actions for the Protection of the Collective Interests of Consumers on the East-Nordic countries’ legislation - Ervo, Laura (Revista Ítalo-Española de Derecho Procesal, 2020)
In this article, it will be discussed how the EU Directive on Representative Actions for the Protection of the Collective Interests of Consumers will affect the East-Nordic countries. In this context, Finland and Sweden are compared. Special emphasis is placed on the current problems concerning class actions vis á vis access to justice and how the new EU Directive will possibly solve the experienced deficiencies. Additionally, the more general perspective on problems in access to justice will be studied from the class-action point of view. Thus, one of the research objectives of this paper is to evaluate whether the current scope of class actions at the national and EU levels is satisfactory and whether there is still space for improvement and additional development at both the EU and national levels.